Structural Behavior of Continuous Steel-Reactive Powder Concrete Composiate Beams Under Repeated Loads - Yassien Dakhil, Rasha; B. Dawood, Mustafa (International Journal of Engineering and Technology, 2018)
A study for the continuous composite steel-reactive powder concrete beams under repeated loads were executed experimentally and analytically. In the experimental part, six continuous composite sections were constructed as test beams. "Theâ€˜â€œdecks slab concretes"was connected tos steel I-beams by headed steel studs welded to the top flangesâ€œofsâ€œthesâ€˜â€˜steel I-beams.â€œT,he dimensionsâ€œ of â€œtheâ€œ deck slab is (2200Ã—250Ã—80mm), while the type of I-beam is (IPE 140) with length of (2200mm). For the present work, the experimental work includes also examining the shear in the links by creating two models (push out) and tested to determine the properties and behavior of the studs. The behavior of the studs were conducted by"getting load-slip curves. In the part of the,oretical,â€˜â€˜.tested beams.was numericallysmodeled then analyzed using thesfinite element method.â€˜â€œThesâ€œnumerical models were carried out in three dimensionss bysâ€œthe software package (ANSYS 16.1). Verifi,cationsof thesnumericalsresultsâ€œwas donesbyscompari,ngs thems with the experimentals results. â€œThesresultssof thesfiniteselementsanalysissshowed good agreementsâ€˜with the results ofsthe experimental tests. The maximumsandsminimum differenceâ€˜â€˜in ultimate loa,ds for beamsâ€˜â€˜ were (5.85% and 1.33%) respectively.Â The results show that stiffenerssof beamssandsstrengthening with CFRP shall increase the ultimate load capacityâ€˜and affects onâ€˜â€˜mode of failureâ€œ of theses beams.â€˜ Â Â